Pendekatan Eskalasi Usaha Perikanan Mas Koki (Carrasius auratus) di Kabupaten Tulungagung - Naning Lailatul Fitriyah; Tutut Dwi Sutiknjo; Eko Yuliarsha Sidhi; Agustia Dwi Pamujiati (JINTAN : Jurnal Ilmiah Pertanian Nasional, 2022)
Goldfish (Carassius auratus) is an ornamental fish with promising agribusiness prospects. One of the cultivation areas with potential for development is Tulungagung Regency. The research was conducted at the Fish Cultivation Group (Pokdakan) Tirto Mulyo Asri, located in Wajak Lor Village, to analyze a particular approach to escalating goldfish culture in the area. The study adopted the Force Field Analysis (FFA) method with a qualitative descriptive analysis approach. The analysis showed five factors driving and inhibiting goldfish cultivation at the research site. The highest driving factor is consumer demand, while the highest inhibiting factor is bad weather conditions, namely the transition season (seasonal shift). The key success factor based on the driving factors for elevated consumer demand means that it focuses on maintaining consumer confidence in the products produced. On the other hand, the key success factor in overcoming the inhibiting factors for bad weather conditions or the transitional season is focusing on weather prediction through collaboration with the government, such as the BMKG. The best approach to halting goldfish culture in the Tirto Mulyo Asri Tulungagung Fish Cultivation Group is to maximize the key driving factors and minimize the key inhibiting factors.